Куртизанка - Моссанен Дора Леви (Грешные желания, 2008)
Экземпляры: Борковская библиотека (20210316) / Инвентарный номер: 10470 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: М 83 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)